Experiencing Lean Six Sigma in the French residential construction: Setting effective performance indicators to address client satisfaction. Issue 4 (10th October 2016) - Dakhli, Zakaria; Lafhaj, Zoubeir; Bos, Antoine
Abstract : Purpose: Compared to the manufacturing industry, Lean Six Sigma (LSS) lacks a clear methodology for its application in the tertiary service. One reason is the difficulties to assess information flow compared to physical flow. Indeed, the use of information flow as a process entry in the LSS method is not well investigated, mainly due to the difficulties in collecting adequate and sufficient data. The purpose of this research study is to investigate the application of LSS in the tertiary service, in particular, real estate development. Design/methodology/approach: The paper is based on an action research methodology where LSS methodology is applied to solve client-dissatisfaction issue. One of its main causes is found to be the late delivery time. The work describes how the method was applied. Findings: LSS is an adequate approach for making well-thought-out improvement in real estate development. Practical implications: The work provides an implementation of LSS in real estate development. It also gives new insights into the LSS application in the tertiary service. The work also suggests practical recommendations and solutions to address the main challenges faced by real estate development. Originality/value: Construction is governed by many processes that are difficult to identify and, even more, to assess. LSS helps identifying those which create real value for the client.